(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In the past two decades, Human Right Law has attainedcrucial importance in the universe and as in demand as never before. With theadvancement the rights of prisoners have also grown manifold which in past wasa discarded and deserted subject.